Optical fiber NO2 gas sensor based on MoS2 supported Au sensitive material, preparation method and application thereof
By adding Au to MoS2, a Mach-Zendel interference fiber NO2 gas sensor was developed, which solved the problems of high lower limit and long response time for low concentration NO2 detection in the prior art, and achieved high sensitivity and low cost NO2 gas detection at room temperature.
Patent Information
- Application Number
- CN202510195319.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-05-02
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing NO2 gas sensors have problems such as high detection lower limit, high heating temperature and long response time in low concentration detection, making it difficult to achieve efficient and low-cost detection at room temperature.
The Mach-Zendel interference fiber NO2 gas sensor based on MoS2-loaded Au-sensitive material is used to improve the sensing performance by adding different proportions of Au to MoS2, and improve the response and detection sensitivity to NO2.
High sensitivity detection of low concentration NO2 at room temperature is achieved, with the lower detection limit as low as 10 ppb, the response time is short, and good selectivity and cost-effectiveness.
Smart Images

Figure CN119915747A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of optical fiber gas sensors, and specifically relates to a Mach-Zehnder interference optical fiber NO2 gas sensor based on MoS2-loaded Au sensitive material, a preparation method and its application in low-concentration NO2 detection. Background Art
[0002] Nitrogen dioxide (NO2) is a harmful air pollutant, mainly produced by the combustion of chemical fuels and factory emissions. It is one of the main factors in the formation of acid rain and photochemical smog, causing serious pollution to rivers, oceans, the earth and the atmosphere. NO2 is colorless and odorless at low concentrations and is harmful to the human respiratory tract. According to the U.S. Occupational Safety and Health Administration, the upper limit of exposure to nitrogen dioxide in factories is 5ppm. It is worth noting that low concentrations of NO2 (1ppm) can damage our lungs and cause serious respiratory diseases with symptoms similar to asthma. Therefore, it is becoming increasingly important and urgent to develop long-term and efficient gas sensors for real-time monitoring of low-concentration NO2 at room temperature.
[0003] At present, the main methods for detecting NO2 include infrared detection and solution absorption. These methods are highly accurate, but the operation methods are complicated, the cost is relatively high, and they cannot be miniaturized and convenient. Gas sensors can complement large instruments due to their advantages such as small size, low cost, and high sensitivity, and have become a research hotspot in the field of gas detection. Traditional gas sensor (chemical resistance type) technology has achieved great success in the detection of NO2, but there are still problems such as insufficient detection limit, high heating temperature, and long response time. In recent years, optical fiber gas sensors coated with different sensitive materials have been widely studied because of their advantages of not being affected by electromagnetic radiation and corrosion, and are used to improve gas sensitivity and selectivity at room temperature. Summary of the invention
[0004] The purpose of the present invention is to provide a Mach-Zehnder interference type optical fiber NO2 gas sensor based on MoS2-supported Au sensitive material, a preparation method and its application in low-concentration NO2 detection.
[0005] The present invention discloses a Mach-Zehnder interferometer optical fiber NO2 gas sensor based on MoS2-supported Au sensitive material. Figure 1 As shown, the interference structure is made of a 15-25 cm long single-mode optical fiber, a 1.5-2.5 mm long coreless optical fiber, a 5-7 cm long thin-core optical fiber, a 1.5-2.5 mm long coreless optical fiber and a 15-25 cm long single-mode optical fiber. The MoS2-supported Au sensitive material is evenly coated on the outside of the thin-core optical fiber. The MoS2-supported Au sensitive material (MoS2-Au) is prepared by the following method:
[0006] Weigh (NH4)6Mo7O according to the molar ratio of Mo to S of 1:3-4 24 ·4H2O and CH4N2S, add deionized water and stir thoroughly, according to (NH4)6Mo7O 24 ·4H2O and polyvinyl pyrrolidone are added in a ratio of 5 to 6:1, stirred until completely dissolved, and then transferred to a hydrothermal reactor for hydrothermal reaction at 160 to 190°C for 20 to 30 hours; then the product is washed several times by ultrasonic vibration and centrifugation with deionized water and anhydrous ethanol, and the product is collected; HAuCl4 solution (a 50 mmol / L aqueous solution prepared by HAuCl4·4H2O) is added to the product at a ratio of Au to MoS2 of 0.01 to 0.1:1, and then NaBH4 is added at a ratio of Au to NaBH4 of 1:5, and stirred continuously at 60 to 80°C in a water bath. After the reaction is complete, the product is washed several times by ultrasonic vibration and centrifugation with deionized water and anhydrous ethanol, and the product is collected and dried to obtain MoS2-supported Au sensitive material (MoS2-Au).
[0007] The preparation method of a Mach-Zehnder interferometer optical fiber NO2 gas sensor based on MoS2-supported Au sensitive material described in the present invention comprises the following steps:
[0008] (1) Making an interference structure: Take a 5-7 cm long thin-core optical fiber and remove its coating; then take two 1.5-2.5 mm long coreless optical fibers and remove their coatings; respectively fusion-splice the two coreless optical fibers with the coating removed to the two ends of the thin-core optical fiber; then take two 15-25 cm long single-mode optical fibers and remove 1-2 cm of coating at one end, and fusion-splice the ends of the two single-mode optical fibers with the coating removed to the two ends of the coreless optical fibers to make the interference structure of the sensor; the other ends of the single-mode optical fibers are respectively connected to a light source and a spectrometer;
[0009] (2) Preparation of sensitive material: measure anhydrous ethanol and deionized water in a volume ratio of 0.9:1-1.2, mix well and add to the MoS2-supported Au sensitive material, and ultrasonically treat for 20-40 min to obtain a 0.1 g / mL concentration of the sensitive material dispersion;
[0010] (3) Making a sensitive element: using a pipette gun, evenly drop-coat the sensitive material dispersion obtained in step (2) on the outer side of the thin-core optical fiber with the interference structure obtained in step (1), and dry it at 60-80° C.; repeat the “drop-coating-drying” operation 3-5 times, thereby obtaining a sensitive layer with a thickness of 2-3 μm on the surface of the thin-core optical fiber;
[0011] (4) Insert the sensitive element obtained in step (3) into the left and right ports of the four-way glass tube to ensure that the sensitive layer is completely in the glass tube, and then seal the left and right ports of the four-way glass tube. The upper and lower ports of the four-way glass tube serve as the air inlet and the air outlet, respectively. Different volumes of NO2 standard gas are injected into the air inlet to adjust the NO2 concentration in the glass tube. The air outlet is connected to an air pump to suck out the detected exhaust gas to achieve repeated testing, thereby preparing a Mach-Zehnder interferometer optical fiber NO2 gas sensor based on MoS2-loaded Au sensitive material.
[0012] The parameters of the single-mode optical fiber, thin-core optical fiber, and coreless optical fiber used in the preparation of the interference structure of the present invention are as follows:
[0013] The cladding diameters of single-mode optical fiber, coreless optical fiber, and thin-core optical fiber are the same, and the ratio of the core diameter of the thin-core optical fiber to the core diameter of the single-mode optical fiber is 1:3 to 4.
[0014] Furthermore, the single-mode optical fiber is from Corning SMF-28, which consists of three parts from the outside to the inside: coating, cladding and core, wherein the coating diameter is 242 microns, the cladding diameter is 125 microns, and the core diameter is 8.2 microns; the cladding material is fluorine-doped quartz, and the core material is 4.5% by mass GeO2-doped silica;
[0015] The coreless optical fiber comes from YOFC CL. It consists of a coating layer and a cladding layer from the outside to the inside. The coating layer has a diameter of 245 microns, the cladding layer has a diameter of 125 microns, and the cladding material is quartz.
[0016] The thin-core optical fiber comes from Nufern 460-HP, which consists of three parts from the outside to the inside: coating, cladding and core. The coating diameter is 245 microns, the cladding diameter is 125 microns, and the core diameter is 2.5 microns; the cladding material is fluorine-doped quartz, and the core material is pure quartz.
[0017] The present invention improves the sensing performance of MoS2 by adding Au in different proportions, thereby improving the response of the sensor to NO2 and shortening the response recovery time. In addition to having high sensitivity, the sensor obtained by the present invention also has a low detection limit, a short response recovery time and good selectivity.
[0018] The sensitive mechanism of the Mach-Zehnder interferometer optical fiber NO2 gas sensor based on MoS2-loaded Au sensitive material can be briefly described as follows: when the light in the light source is transmitted from the single-mode fiber to the coreless fiber, the end face reflection caused by fusion is reduced. When the light reaches the thin-core fiber through the coreless fiber, since the core diameter of the thin-core fiber is much smaller than the core diameter of the single-mode fiber, the cores of the two optical fibers do not match, and the various cladding modes of the light will be activated, causing part of the light to be coupled into the core of the thin-core fiber for propagation. Since this part of the light is almost not affected by external information, the light propagated in the core can be used as the reference arm of the Mach-Zehnder interferometer; while the other part of the light, due to the effect of the evanescent field, evanescently propagates in the cladding of the thin-core fiber and the sensitive layer coated outside the cladding. The light propagated can be used as the signal arm of the Mach-Zehnder interferometer; when the two beams of light transmitted in the reference arm and the signal arm pass through the coreless optical fiber again to reach the single-mode optical fiber, the light propagating in the core and the evanescent light propagating in the cladding and the sensitive layer coated outside the cladding enter the core of the single-mode optical fiber and propagate; when the NO2 gas molecules come into contact with the sensitive layer, the effective refractive index of the light propagating in the cladding and the sensitive layer changes. As the concentration of NO2 gas molecules increases, the effective refractive index of the light propagating in the cladding and the sensitive layer increases, while the effective refractive index of the light propagating in the core remains unchanged. The difference in the refractive indices of the two beams of light decreases, resulting in a decrease in the phase difference, while the cosine value of the phase difference increases, which ultimately leads to an increase in the interference light intensity of the interference spectrum generated in the spectrometer. Therefore, the measurement of the interference light intensity can be used to detect gas concentration. The calculation formula for the interference spectrum intensity is as follows:
[0019]
[0020] Where I1 and I2 are the intensity of light propagating in the core and the intensity of light propagating in the cladding and sensitive layer, respectively. is the phase difference between the two modes of light. It can also be obtained by the following formula:
[0021]
[0022] in are the effective refractive index of light propagating in the core and the effective refractive index of light propagating in the cladding and sensitive layer, respectively, and L is the length of the thin core fiber coupled into the single-mode optical fiber.
[0023] The NO2 gas sensor prepared by the present invention using MoS2-supported Au sensitive material as the sensitive material has the excellent characteristics of room temperature detection, low cost, high sensitivity, good selectivity and low detection limit (10ppb).
[0024] Advantages of the present invention:
[0025] (1) The present invention uses light intensity changes as a measure of gas concentration changes. Compared with other types of sensors, it has the advantages of working at room temperature, good selectivity, and a low detection limit (10 ppb, such as Figure 4 As shown), fast response time, etc.
[0026] (2) The present invention adds Au to the sensitive layer and achieves the purpose of improving the response speed and response size of the sensor by changing different loading ratios (the response is defined as the difference between the light intensity at a fixed wavelength valley of the sensor after different concentrations of NO2 are introduced into the interference spectrum and the light intensity at the same location of the sensor in the air atmosphere), so that the sensor can also work at a relatively low concentration (10ppb to 5ppm, such as Figure 4 In the NO2 gas environment shown in the figure, the problems of high detection limit and high working temperature existing in the existing NO2 sensor are solved;
[0027] (3) The present invention adopts an optical fiber sensor structure, which has the advantages of small size, low cost, simple preparation, and is suitable for mass industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 : Schematic diagram of a Mach-Zehnder interferometer optical fiber NO2 gas sensor using the MoS2-supported Au sensitive material as the sensitive material of the present invention;
[0029] Figure 2 : Schematic diagram of the NO2 gas sensor test prepared by the present invention;
[0030] Names of each part: continuous broadband light source 1, four-way glass tube 2, optical fiber spectrometer 3, micro air pump 4, single-mode optical fiber 5, thin-core optical fiber 6, coreless optical fiber 7, sensitive film 8;
[0031] like Figure 2 As shown in the figure, after the sensor is fixed on the four-way glass tube, one end of the single-mode optical fiber is connected to a continuous broadband light source (NKT photonics), and the other end is connected to a fiber spectrometer (AQ6370D Yokogawa). The upper port of the four-way glass tube is used as an air inlet. Different volumes of NO2 standard gas are injected into the glass tube as needed, so that different concentrations of NO2 gas are configured in the glass tube for testing; the lower port of the glass tube is connected to a micro air pump to extract the internal exhaust gas after the test is completed;
[0032] Figure 3 : XRD pattern of the sensitive electrode material prepared by the present invention (the horizontal axis is the angle, the vertical axis is the intensity);
[0033] like Figure 3As shown, the diffraction peaks of each sensitive electrode material correspond well to the MoS2 standard card 2-1133MoS2. There is a certain offset at the characteristic peak, which is caused by some curling at the edge of the flake MoS2. At the same time, there are some tiny miscellaneous peaks, which is because in order to ensure that the material can form a suspension and be coated on the outside of the optical fiber, it is not sintered. The characteristic peaks of MoS2-1%Au, MoS2-2%Au, MoS2-5%Au, and MoS2-10%Au correspond well to the standard card 60-2870 of Au, indicating that Au is well supported in the MoS2 material;
[0034] Figure 4 : The interference spectrum of the NO2 gas sensor prepared by the present invention measured by a fiber optic spectrometer (AQ6370D Yokogawa) in an air atmosphere and in a NO2 gas concentration range of 10ppb to 5ppm after being connected to a continuous broadband light source (NKT photonics);
[0035] like Figure 4 As shown, when the wavelength of the gas sensor is 1570nm, the absolute value of the light intensity is the smallest in the air atmosphere, which is 31.1db; as the NO2 gas concentration in the glass tube increases from 10ppb to 5ppm, the absolute value of the light intensity continues to increase, and the absolute value of the light intensity is the largest in the 5ppm NO2 atmosphere, which is 33.5db;
[0036] Figure 5 : Response recovery curves of sensors made of MoS2, MoS2-1%Au, MoS2-2%Au, MoS2-5%Au, and MoS2-10%Au sensitive materials to 10-5000ppb NO2;
[0037] like Figure 5 As shown in the figure, the response value ΔIntensity is defined as the difference between the light intensity of the sensor in the measured gas and the light intensity of the sensor in the air at the same trough position of the interference spectrum. Among them, the horizontal axis is time, the vertical axis is the response value, the working temperature is room temperature, and the device made of MoS2-5% Au as the sensitive material has the largest response value for NO2 and exhibits the best gas sensing performance.
[0038] Figure 6 : Response recovery curve of the sensor using MoS2-5%Au as sensitive material to 5ppm NO2 (wherein the horizontal axis is time, the vertical axis is the response value, and the operating temperature is room temperature);
[0039] like Figure 6 As shown, the response recovery time of the device to 5ppm NO2 is 21s and 16s respectively.
[0040] Figure 7:Selectivity bar graph of the sensor using MoS2-5%Au as sensitive electrode material for different gases at 5ppm;
[0041] like Figure 7 As shown, the device made of MoS2-5% Au as the sensitive electrode material has good selectivity, and the response value to 5ppm NO2 gas is much higher than that to other gases (NH3, SO2, CO, H2S). Therefore, the device has good anti-interference ability in an environment where multiple gases coexist.
[0042] Figure 8 : Stability curve of the device made of MoS2-5%Au as sensitive material to 5ppmNO2 (where the horizontal axis is time and the vertical axis is response value);
[0043] like Figure 8 As shown, the stability test of the device made of MoS2-5% Au as the sensitive material was carried out within 15 days. It can be seen from the figure that the fluctuation range of the response value of the device is small within 15 days, which shows that the device has good stability.
[0044] Fig. 9 : The repeatability curve of the device made of MoS2-5%Au as the sensitive material to 5ppm NO2 (where the horizontal axis is the five prepared devices and the vertical axis is the response value;
[0045] like Fig. 9 As shown, it is the repeatability test of five groups of devices made with MoS2-5% Au as sensitive material. It can be seen from the figure that the fluctuation range of the response value of 5ppm NO2 of the five groups of devices prepared in the same way is small, indicating that the device has good repeatability. DETAILED DESCRIPTION
[0046] Embodiment 1:
[0047] MoS2 material was prepared by hydrothermal method, and MoS2-5% Au material was prepared by sodium borohydride reduction method. It was used as sensitive material to make MZI interferometric NO2 sensor, and the gas sensitive performance of the sensor was tested. The specific process is as follows:
[0048] (1) Making an interference structure: Take a 6-cm-long Nufern 460-HP fine-core optical fiber with a cladding diameter of 125 μm and a core diameter of 2.5 μm, then take two 2-mm-long coreless optical fibers with a cladding diameter of 125 μm, use optical fiber strippers to remove the coating layers of the fine-core optical fiber and the coreless optical fiber, and use a fusion splicer to fusion-splice the two coreless optical fibers to the two ends of the fine-core optical fiber; then take two 20-cm-long Corning SMF-28 single-mode optical fibers with a cladding diameter of 125 μm and a core diameter of 8.2 μm, remove the coating layers of 2 cm at one end of each, and fusion-splice the ends without the coating layers to the other ends of the coreless optical fibers to make the interference structure of the sensor; the other ends of the single-mode optical fibers are connected to a continuous broadband light source 1 and a fiber spectrometer 3, respectively;
[0049] (2) Preparation of sensitive materials: First, MoS2 was prepared by hydrothermal method, and (NH4)6Mo7O was weighed in a ratio of Mo to S of 1:3. 24 ·4H2O and CH4N2S, add deionized water and stir thoroughly, then follow the (NH4)6Mo7O 24 ·4H2O and polyvinyl pyrrolidone were added in a ratio of 5:1, and the mixture was stirred until completely dissolved. Then, it was transferred to a 100mL stainless steel autoclave lined with polytetrafluoroethylene and placed in an oven for hydrothermal reaction at 180°C for 24h. The product was then washed several times with deionized water and anhydrous ethanol by ultrasonic vibration and centrifugation, and the product was collected. Then, different volumes of 50mmol / L HAuCl4 solution were added dropwise according to the mass ratio of Au to MoS2 of 0:1, 0.01:1, 0.02:1, 0.05:1, and 0.1:1, respectively. NaBH4 was added in a mass ratio of Au to NaBH4 of 1:5, and the mixture was stirred continuously in a water bath at 80°C until the reaction was complete, and the product was washed several times by ultrasonic centrifugation with deionized water and anhydrous ethanol to obtain a sensitive material; according to the different amounts of HAuCl4 used, they were recorded as MoS2, MoS2-1% Au, MoS2-2% Au, MoS2-5% Au, and MoS2-10% Au respectively; anhydrous ethanol and deionized water with a volume ratio of 0.9:1 were measured, and the above-mentioned sensitive materials were added, and a dispersion of the sensitive material with a concentration of 0.1 g / mL was obtained after ultrasonic treatment for 30 minutes;
[0050] (3) coating sensitive material: fix the interference structure obtained in step (1) on a glass plate, use a dropper to absorb 2 mL of the sensitive material dispersion obtained in step (2), evenly drip it on the outside of the thin-core optical fiber of the interference structure, and dry it in an oven at 60° C. for 60 min; repeat the "drip coating-drying" operation steps three times to obtain an interference structure coated with a sensitive layer with a thickness of 2 to 3 μm;
[0051] (4) Insert the interference structure obtained in step (3) into the left and right ends of the four-way glass tube, ensure that the 6 cm long thin-core optical fiber area is completely inside the glass tube, and seal the left and right ends of the glass tube with a glue gun; connect the upper end of the glass tube to a 4 cm rubber tube as an air inlet and clamp it with a water stop clamp, and inject different volumes of NO2 standard gas into the glass tube as needed to obtain NO2 gas of different concentrations; connect the lower end of the glass tube to a micro air pump through a rubber tube to extract the internal exhaust gas after the test is completed;
[0052] (5) The single-mode optical fiber of the NO2 sensor obtained in step (4) is connected to a continuous broadband light source (NKT photonics) and an optical fiber spectrometer (AQ6370D Yokogawa) (eg Figure 1 ), by injecting different volumes of NO2 at the air inlet and exhausting air at the air outlet, the sensor was placed in air and different concentrations of NO2 atmosphere for spectral signal testing.
Claims
1. A Mach-Zehnder interferometry optical fiber NO2 gas sensor based on MoS2-supported Au sensitive material, characterized in that: The interference structure is made of single-mode optical fiber, coreless optical fiber, thin-core optical fiber, coreless optical fiber and single-mode optical fiber in sequence. The MoS2-supported Au sensitive material is evenly coated on the outside of the thin-core optical fiber. The MoS2-supported Au sensitive material is prepared by the following method: Weigh (NH4)6Mo7O according to the molar ratio of Mo to S of 1:3-4 24 ·4H2O and CH4N2S, add deionized water and stir thoroughly, according to (NH4)6Mo7O 24 ·4H2O and polyvinyl pyrrolidone are added in a ratio of 5 to 6:1, stirred until completely dissolved, and then transferred to a hydrothermal reactor for hydrothermal reaction at 160 to 190°C for 20 to 30 hours; then the product is washed several times by ultrasonic centrifugation with deionized water and anhydrous ethanol, and the product is collected; HAuCl4 solution with a concentration of 50 mmol / L is added to the product according to a mass ratio of Au to MoS2 of 0.01 to 0.1:1, and then NaBH4 is added according to a mass ratio of Au to NaBH4 of 1:5, and stirred continuously at 60 to 80°C in a water bath. After the reaction is complete, the product is washed several times by ultrasonic centrifugation with deionized water and anhydrous ethanol, and the product is collected and dried to obtain MoS2-supported Au sensitive material.
2. A Mach-Zehnder interferometer optical fiber NO2 gas sensor based on MoS2-supported Au sensitive material according to claim 1, characterized in that: The length of single-mode optical fiber is 15 to 25 cm, the length of coreless optical fiber is 1.5 to 2.5 mm, and the length of thin-core optical fiber is 5 to 7 cm; the cladding diameters of single-mode optical fiber, coreless optical fiber, and thin-core optical fiber are the same, and the ratio of the core diameter of thin-core optical fiber to the core diameter of single-mode optical fiber is 1:3 to 4.
3. The Mach-Zehnder interferometer optical fiber NO2 gas sensor based on MoS2-supported Au sensitive material according to claim 1, characterized in that: The single-mode optical fiber consists of three parts from the outside to the inside: the coating, the cladding and the core. The diameter of the coating is 242 microns, the diameter of the cladding is 125 microns, and the diameter of the core is 8.2 microns. The cladding material is fluorine-doped quartz, and the core material is 4.5% GeO2-doped silica. The coreless optical fiber is composed of a coating layer and a cladding layer from the outside to the inside, wherein the coating layer has a diameter of 245 microns, the cladding layer has a diameter of 125 microns, and the cladding layer material is quartz; The thin-core optical fiber consists of three parts from the outside to the inside: the coating, the cladding and the core. The coating diameter is 245 microns, the cladding diameter is 125 microns, and the core diameter is 2.5 microns. The cladding material is fluorine-doped quartz and the core material is pure quartz.
4. A method for preparing a Mach-Zehnder interferometer optical fiber NO2 gas sensor based on MoS2-supported Au sensitive material according to any one of claims 1 to 3, wherein the steps are as follows: (1) Making an interference structure: Take a section of fine-core optical fiber and remove its coating; then take two sections of coreless optical fiber and remove their coating; respectively fusion-splice the two sections of coreless optical fiber with the coating removed to the two ends of the fine-core optical fiber; then take two sections of single-mode optical fiber and remove 1 to 2 cm of coating at one end of each section, and respectively fusion-splice the ends of the two sections of single-mode optical fiber with the coating removed to the two ends of the coreless optical fiber to make an interference structure of the sensor; (2) Preparation of sensitive material: measure anhydrous ethanol and deionized water in a volume ratio of 0.9:1-1.2, mix well and add to the MoS2-supported Au sensitive material, and ultrasonically treat for 20-40 min to obtain a 0.1 g / mL concentration of the sensitive material dispersion; (3) Making a sensitive element: using a pipette gun, evenly drop-coat the sensitive material dispersion obtained in step (2) on the surface of the thin-core optical fiber with the interference structure obtained in step (1), and dry it at 60 to 80° C.; repeat the "drop-coating-drying" operation 3 to 5 times, thereby obtaining a sensitive layer with a thickness of 2 to 3 μm on the surface of the thin-core optical fiber; (4) Insert the sensitive element obtained in step (3) into the left and right ports of the four-way glass tube to ensure that the sensitive layer is completely in the glass tube, and then seal the left and right ports of the four-way glass tube. The upper and lower ports of the four-way glass tube serve as the air inlet and the air outlet, respectively. Different volumes of NO2 standard gas are injected into the air inlet to adjust the NO2 concentration in the glass tube. The air outlet is connected to an air pump to suck out the detected exhaust gas to achieve repeated testing, thereby preparing a Mach-Zehnder interferometer optical fiber NO2 gas sensor based on MoS2-loaded Au sensitive material.
5. Application of a Mach-Zehnder interferometry optical fiber NO2 gas sensor based on MoS2-supported Au sensitive material as described in any one of claims 1 to 3 in low-concentration NO2 detection.
6. The application of a Mach-Zehnder interferometer optical fiber NO2 gas sensor based on MoS2-supported Au sensitive material in low-concentration NO2 detection as claimed in claim 5, characterized in that: The concentration of NO2 is 10ppb~5ppm.
Citation Information
Patent Citations
Au@MoS2-based localized surface plasma enhanced NO2 gas sensor and preparation method thereof
CN113125385A
Graphene oxide optical fiber humidity sensor
CN114609089A
Optical fiber NO2 gas sensor based on MoS2-ZnO composite material
CN217484166U
SMF-NCF-FMF-TCF-FBG fiber laser temperature sensor based on dislocation structure
CN220230751U